Owners’ graffiti on pottery from Tissamaharama - Falk, Harry (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
Almost twenty years of excavation at Tissamaharama, southern Sri Lanka, have produced an immense number of pottery sherds. More than one hundred carry comprehensible legends in Brāhmī letters, dating back to centuries before and after Christ. They allow for the fi rst time to accompany the Buddhist monks and nuns in their numerical development over centuries and their interaction with sponsors and supporters. Nunneries are otherwise almost untraceable, while here we have a domination of nuns and laywomen over their male counterparts. Tamil speaking components of society are few but perceptible, particularly during the foundation phase.The article will be available as a PDF in the near future.